PENERAPAN TRAIT AND FACTOR UNTUK MENINGKATKAN KONSENTRASI BELAJAR DARING KELAS XI SMK N 3 KUDUS - Nafi' Dyah Ristanti; Arista Kiswantoro; Sumarwiyah Sumarwiyah (Universitas Muria Kudus, 2022)
This research was motivated by the problem of low learning concentration during online learning in class XI APHP 1 SMK N 3 Kudus which resulted in disruption of the online learning process. The objectives to be achieved in this research are: 1. Finding factors that can affect low learning concentration during online learning in class XI students of SMK N 3 Kudus, 2. Increasing learning concentration during online learning. Trait and Factor Counseling is a trait or trait referring to individual characteristics that can be measured such as the ability, talent, character, traits that cause something to happen. This research uses a case study qualitative research approach. The case study steps are: case data collection, case identification, analysis, diagnosis, prognosis, treatment, and follow-up. Data collection was done by interview, observation, and documentation. Based on the research results, trait and factor counseling can help students improve concentration in online learning.